A case of pregnancy complicated with congenital dysprothrombinemia (prothrombin Tokushima). Issue 7 (October 2015) - Maeda, Kazuhisa; Kaji, Takashi; Kasai, Kana; Nakayama, Soichiro; Morine, Mikio; Irahara, Minoru
<x xml:space="preserve">Abstract</x> We present the course of pregnancy and delivery in a patient with congenital dysprothrombinemia. The patient is a 29-year-old nulliparous woman. She was diagnosed with dysprothrombinemia at 10 years of ag. Her course of pregnancy was uneventful. She delivered after prophylactic lyophilized human blood coagulation factor IX complex 800 U was administered. The plasma prothrombin activity was at 24.0% of normal plasma clotting activity. Her postpartum course was uneventful. After 6 years, her course of pregnancy was the same as before. Prophylactic lyophilized human blood coagulation factor IX complex 800 U was administered. Her plasma prothrombin activity was at 26.7%, and she underwent an induced delivery. Her postpartum course was uneventful. It is beneficial to use prophylactic lyophilized human blood coagulation factor IX complex 800 U in pregnancies that are complicated by dysprothrombinemia. The goal of therapy is to maintain prothrombin levels at above 20%.